Field reports, Mark Proescholdt, fall 1989 - Proescholdt, Market al (1989)
Field reports form for fall 1989 submitted by Mark Proescholdt with several other observers along with an introductory letter. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of fall 1989. Epson - sheet feed